A woman of adventure the life and times of First Lady Lou Henry Hoover - Dunlap, Annette, 1955- ([Lincoln] : Potomac Books, an imprint of the University of Nebraska Press, 2022)
Annette B. Dunlap takes a fresh look at Lou Henry Hoover, the First Lady who preceded Eleanor Roosevelt, from Hoover's relief efforts during World War I to her work developing organizations that promoted self-sufficiency among young girls and women.
Cover -- Title Page -- Copyright Page -- Contents -- List of Illustrations -- Acknowledgments -- Introduction -- 1. Avid Outdoorswoman -- 2. The Frustration of Being a Groundbreaker -- 3. Newlywed in China -- 4. Challenging Years -- 5. Power Couple -- 6. A World and a Marriage Transformed -- 7. A New Life's Purpose -- 8. Time of Transition -- 9. The Wearer of Many Hats -- 10. An Organizational Powerhouse -- 11. The Trail to the White House -- 12. An Independent-Minded First Lady -- 13. Volunteerism and Private Philanthropy -- 14. Out of the Limelight -- 15. No Finer Example -- Notes -- Index
JSTOR
Keywords: Girl Scouts of the United States of America -- Biography; Hoover, Herbert, -- 1874-1964.; Hoover, Lou Henry, -- 1874-1944.; Hoover, Herbert, -- 1874-1964.; Hoover, Lou Henry, -- 1874-1944.; Hoover, Lou Henry, -- 1874-1944; Hoover, Herbert, -- 1874-1964; Girl Scouts of the United States of America; Presidents' spouses -- United States -- Biography; California -- Biography; Californie -- Biographies; SOCIAL SCIENCE / Philanthropy & Charity; BIOGRAPHY & AUTOBIOGRAPHY / Women; Presidents' spouses; California; United States; Biographies